A Profile on Medico-legal Cases Reported at a Tertiary Care Centre in the Coastal Town of South Karnataka - Saji, S; Nayak, VC (Journal of Indian Academy of Forensic Medicine, 2024)
The National Medical Council of India has officially renamed Casualty as Emergency Department and as the name suggests it is equipped to handle any incoming trauma into a hospital. Some cases unlike others have a legal aspect to it apart from it being a medical emergency. A retrospective cross-sectional of medico-legal cases recorded from 1st January 2020 to 31st December 2021 was conducted at Kasturba Medical College and Hospital, Manipal. Through this study, such cases labeled medico-legal are evaluated based on Age, Gender, and Type of Cases. Consequently, aim to reduce the frequency of such cases reported, by understanding the risk factors at the helm and thus aid in spreading awareness among the general public to curtail the causative factors so responsible.
Keywords: Medico-legal; Tertiary Care; Road Traffic Accidents; Assault